The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/1475-6765.12238
|View full text |Cite
|
Sign up to set email alerts
|

Electoral infidelity: Why party members cast defecting votes

Abstract: Party politics and electoral research generally assume that party members are loyal voters. This article first assesses the empirical basis for this assumption before providing individual-level explanations for defection. We combine prominent theories from party politics and electoral behavior research and argue that internal disagreement and external pressure can each bring about disloyal voting. We motivate our hypotheses with multi-country European survey data and test them on two sets of party-level nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In this concept, party members play an important role for the effective functioning of the party (Scarrow, 2015; Webb, 2000). They provide the party, for example, with a strong linkage to the electorate by offering input for party policy and ideology, by acting as activists and volunteers during election campaigns and by presenting a reservoir of mostly stable voters (Polk and Kölln, 2018). Beyond the benefits members offer to their parties, members – and party affiliates in general – are said to contribute to democratic legitimacy because they are advocates of parties as political institutions, and this should reflect itself in a more positive attitude towards the political system (Anderson and Just, 2013; Muirhead, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In this concept, party members play an important role for the effective functioning of the party (Scarrow, 2015; Webb, 2000). They provide the party, for example, with a strong linkage to the electorate by offering input for party policy and ideology, by acting as activists and volunteers during election campaigns and by presenting a reservoir of mostly stable voters (Polk and Kölln, 2018). Beyond the benefits members offer to their parties, members – and party affiliates in general – are said to contribute to democratic legitimacy because they are advocates of parties as political institutions, and this should reflect itself in a more positive attitude towards the political system (Anderson and Just, 2013; Muirhead, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on this idea, Weber (2011) and Kang (2004) show that the term can also be used to describe the diverse set of criteria that citizens use to evaluate political parties. For instance, quality may refer to party leadership (see, for example, Polk and Kölln, 2018), policy congruence (Myatt, 2017) or the ability of parties to handle voters' most important issues (Weber, 2011). But while there are multiple manifestations of quality in politics, the mechanism is identical across all of them (Weber, 2011: 910): supporters of parties who perceive that their most preferred party fails to live up to the supporters' standards become more likely to cast an insincere vote to signal their dissatisfaction-that is, they cast a protest vote.…”
Section: Protest Voting-basic Mechanism and Expected Election Resultsmentioning
confidence: 99%
“…8Leader evaluations may also contribute to voters’ willingness to defect, as a study on party members in Sweden and Great Britain by Polk and Kölln (2018) has shown. However, comparative research highlights the difficulties of teasing out leader effects (Mughan, 2015), which is the reason I focused on other sources of protest voting in this article.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a strong identifier will want to adhere to the norms and behaviours in their peer-group and will likely be more receptive to party elites' call to action than non-committed individuals. Second, previous research has shown that ideological congruence between members and parties is positively related to degrees of activism (Lisi and Cancela, 2019;Polk and Kölln, 2017;van Haute and Carty, 2012). Insofar as strength of party identification taps into a similar (albeit perceived) connection between parties and their adherents, we would expect our findings to run in the same direction.…”
Section: Theoretical Framework and Research Designmentioning
confidence: 97%